"As manifestações de junho de 2013 pra gente não acabou" : um estudo sobre as formas de contestação no Coletivo Debaixo em Aracaju - Santos, Jonatha Vasconcelos (2017)
This dissertation analyzes the emergence and dynamics of contestation of the Coletivo Debaixo between the years of 2013 and 2016 in Aracaju. The Coletivo Debaixo appears after the manifestations of June of 2013, known in the city as Acorda Aracaju, through the monthly occupation titled Sarau Debaixo in the Viaduct Journalista Carvalho Déda, popularly known like “Viaduto do DIA”. This research also demonstrates, from the Coletivo Debaixo, the process of emergence of a collective that results from the cycle of protests of 2013 and that, in this sense, is also a consequence of a process of elaboration of a collective action model which has as main repertoire of collective action the occupation of the public space with the use of forms of aesthetic contestation. Along with this, the collective uses, and also elaborates, a grammar of contestation that is based on the notion of the "unequal city" and need of resumption of the public space that is a very recurrent agenda among the social movements from the manifestations of 2013. The collective is formed by young people, almost all university students, who have two common elements in their life histories, their involvement with forms of artistic expression such as the punk movement, poetry and hip-hop and previous participation in social movements, political parties and other collectives. These common events among the life stories of the members of the collective mark the forms of action and organizational models triggered by the group. The monthly occupation of the viaduct, the third tuesday of the month, during those years contributed to the creation of a contestation routine that began to be experienced by a group of actors already mobilized in social movements, political and collective parties, as well as sympathizers. This monthly routine, a form found by the collective to keep as manifestations of 2013 on the streets beyond that year, was responsible for identifying the viaduct as a new "political place". This "political place" underwent a dynamics of re-signification of its public space that occurs during the three years of mobilization. After that, the viaduct is recognized by other social movements in one place to be used for a claim in various ways. In this sense, this research is part of a field of research on the developments of the 2013 protest cycle in Brazil, such as the emergence of new mobilized groups and the expansion of forms of political participation.